Association of inflammatory blood markers and pathological complete response in HER2-positive breast cancer: a retrospective single-center cohort study - Chen, Xiaobin; Cai, Qindong; Deng, Lin; Chen, Minyan; Xu, Min; Chen, Lili; Lin, Yuxiang; Li, Yan; Wang, Yali; Chen, Hanxi; Liu, Shunyi; Wu, Jinqiao; et al. (Frontiers in Immunology, 2024)
IntroductionThe association between inflammatory blood markers (IBMs) (monocyte-to-lymphocyte ratio [MLR], neutrophil-to-lymphocyte ratio [NLR], and platelet-to-lymphocyte ratio [PLR]) and breast cancer has been extensively studied. However, the predictive role of IBMs in the neoadjuvant response of human epidermal growth factor receptor 2 (HER2)-positive breast cancer remains unclear.MethodsThis study included 744 patients with HER2 positive breast cancer treated with neoadjuvant therapy. Baseline MLR, NLR, and PLR data were collected to investigate the association between IBMs and pathological complete response (pCR).ResultsMLR, NLR, and PLR were not associated with neoadjuvant response in the overall population before and after matching. Subgroup analysis stratified by neoadjuvant therapy suggested that these IBMs play a diverse predictive role in response to chemotherapy alone and chemotherapy plus anti-HER2 therapy. A high MLR and NLR, but not PLR, were associated with lower pCR rates in HER2-targeted therapy (MLR: OR=0.67, P=0.023; NLR: OR=0.665, P=0.02; PLR: OR=0.801, P=0.203). Among the anti-HER2 treatment population, patients with a high MLRs (pCR rate, 40.2%) could be divided into MLRhigh/NLRhigh (pCR rate, 36.3%) and MLRhigh/NLRlow (pCR rate, 48.9%) groups when the NLR was considered. The pCR rates of the MLRhigh/NLRlow and low-MLR groups were similar (pCR rate, 47.6%). A comparable stratification effect was observed in patients with high NLR.ConclusionsIBMs play a diverse predictive role in pCR in HER2-positive breast cancer stratified by neoadjuvant regimens. The combination of high MLR and high NLR enabled better identification of patients with poor responses to anti-HER2 therapy than high MLR or NLR alone.